A case–control study to estimate the effects of acute clinical infection with the Schmallenberg virus on milk yield, fertility and veterinary costs in Swiss dairy herds - Wüthrich, M.; Lechner, I.; Aebi, M.; Vögtlin, A.; Posthaus, H.; Schüpbach-Regula, G.; Meylan, M. (Preventive veterinary medicine, 2016)
Schmallenberg virus (SBV) was first detected in Switzerland in July 2012 and many Swiss dairy farmers reported acute clinical signs in dairy cattle during the spread of the virus until December 2012. The objectives of the present study were to investigate the effects of an acute infection with SBV on milk yield, fertility and veterinary costs in dairy farms with clinical signs of SBV infection (case farms), and to compare those farms to a matched control group of dairy farms in which cattle did not show clinical signs of SBV infection. Herd size was significantly (p<0.001) larger in case farms (33 cows, n=77) than in control farms (25 cows, n=84). Within case herds, 14.8% (median) of the cows showed acute clinical signs. Managers from case farms indicated to have observed a higher abortion rate during the year with SBV (6.5%) than in the previous year (3.7%). Analysis of fertility parameters based on veterinary bills and data from the breeding associations showed no significant differences between case and control farms. The general veterinary costs per cow from July to December 2012 were significantly higher (p=0.02) in case (CHF 19.80; EUR 16.50) than in control farms (CHF 15.90; EUR 13.25). No differences in milk yield were found between groups, but there was a significant decrease in milk production in case farms in the second half year in 2012 compared to the same period in 2011 (p<0.001) and 2013 (p=0.009). The average daily milk yield per cow (both groups together) was +0.73kg higher (p=0.03) in the second half year 2011 and +0.52kg (p=0.12) in the second half year 2013 compared to the same half year 2012. Fifty-seven percent of the cows with acute clinical signs (n=461) were treated by a veterinarian. The average calculated loss after SBV infection for a standardized farm was CHF 1606 (EUR 1338), which can be considered as low at the national level, but the losses were subject to great fluctuations between farms, so that individual farms could have very high losses (>CHF 10,000, EUR 8333).